2012
DOI: 10.1192/bjp.bp.111.092007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anti-basal ganglia antibodies in adult obsessive–compulsive disorder: cross-sectional study

Abstract: BackgroundSymptoms of obsessive–compulsive disorder (OCD) have been described in neuropsychiatric syndromes associated with streptococcal infections. It is proposed that antibodies raised against streptococcal proteins cross-react with neuronal proteins (antigens) in the brain, particularly in the basal ganglia, which is a brain region implicated in OCD pathogenesis.AimsTo test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 35 publications
3
47
0
2
Order By: Relevance
“…Inflammation, oxidative stress, and immunological abnormality have been highlighted in various psychiatric disorders (Ng et al, 2008; Pasco et al, 2010; Kato et al, 2011a; Maes et al, 2011, 2012; Davison, 2012; Nicholson et al, 2012). The pathophysiology of psychiatric disorders has been dominantly believed to be solely explained by abnormalities of neurotransmitter systems.…”
Section: Psychiatric Disorders and Microgliamentioning
confidence: 99%
“…Inflammation, oxidative stress, and immunological abnormality have been highlighted in various psychiatric disorders (Ng et al, 2008; Pasco et al, 2010; Kato et al, 2011a; Maes et al, 2011, 2012; Davison, 2012; Nicholson et al, 2012). The pathophysiology of psychiatric disorders has been dominantly believed to be solely explained by abnormalities of neurotransmitter systems.…”
Section: Psychiatric Disorders and Microgliamentioning
confidence: 99%
“…Studies conducted in both pediatric and adult OCD patients found higher levels of antibasal ganglia antibodies and antithalamic autoantibodies compared with the control group (Dale et al, 2005; Pearlman et al, 2014). In addition, antibasal ganglia antibody was found in both seropositive (antistreptolysin O-positive) and seronegative OCD patients (Nicholson et al, 2012). Consistent with these findings, functional abnormalities in the cortico-striato-thalamo-cortical circuitry in OCD were also reported (Pittenger et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Nicholson et al [34] tested 96 adult OCD patients and 50 controls (33 with chronic depression and 17 with schizophrenia) for the presence of ASO and ABGA. The rates of positivity for ASO in both the OCD and control groups were low and the differences were not significant.…”
Section: Abga: More Than a Biomarker?mentioning
confidence: 99%